A novel curcumin-loaded nanoparticle restricts atherosclerosis development and promotes plaques stability in apolipoprotein E deficient mice. (February 2019) - Meng, Ning; Gong, Yan; Zhang, Jiefeng; Mu, Xin; Song, Zhimei; Feng, Runliang; Zhang, Hua
Although curcumin possesses anti-atherogenic and anti-inflammatory properties, its application is limited because of its low aqueous solubility and poor oral bioavailability. Recently, our group synthesized a novel linear-dendrimer methoxy-poly (ethylene glycol)-b-poly(ε-caprolactone) copolymer nanoparticle loading curcumin (Cur-NPs) which could improve solubility and release property of curcumin. In the present study, we further evaluated its anti-atherosclerotic effect in apolipoprotein E −/− mice. Our results demonstrated that the Cur-NPs significantly decreased atherosclerotic lesion areas and were more effective in stabilizing vulnerable plaques compared with free curcumin. The anti-atherosclerotic mechanisms of Cur-NPs include decreasing the number of introplaque microvessels, inhibiting the matrix metalloproteinase 2 and 9 activity, reducing the inflammatory response and regulating lipoprotein cholesterol metabolism more effectively compared with free curcumin. Furthermore, Cur-NPs could increase the amount of curcumin in the thoracic aorta and no significant toxicity was observed in the blood biochemical parameters in Cur-NPs-treated groups. Overall, our findings suggested that Cur-NPs could be a stabilized aqueous formulation for application with improved curcumin activity, which could be a potential treatment strategy for arteriosclerosis in the future.